2021
DOI: 10.1128/jvi.00166-21
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Uncoating Occurs via a Series of Rapid Biomechanical Changes in the Core Related to Individual Stages of Reverse Transcription

Abstract: The HIV core consists of the viral genome and associated proteins encased by a cone-shaped protein shell termed the capsid. Successful infection requires reverse transcription of the viral genome and disassembly of the capsid shell within a cell in a process known as uncoating. The integrity of the viral capsid is critical for reverse transcription, yet the viral capsid must be breached to release the nascent viral DNA prior to integration. We employed atomic force microscopy to study the stiffness changes in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…Recently we analyzed the effects of IP6 on the dynamics of HIV-1 core stiffness changes during ERT [ 66 ]. Addition of IP6 to purified cores increased their stiffness even in the absence of reverse transcription, consistent with its capsid stabilizing effect.…”
Section: Reverse Transcription Promotes Hiv-1 Uncoatingmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently we analyzed the effects of IP6 on the dynamics of HIV-1 core stiffness changes during ERT [ 66 ]. Addition of IP6 to purified cores increased their stiffness even in the absence of reverse transcription, consistent with its capsid stabilizing effect.…”
Section: Reverse Transcription Promotes Hiv-1 Uncoatingmentioning
confidence: 99%
“…Moreover, addition of IP6 and the CA-targeting inhibitor PF74 stiffens the capsid. Using AFM operating in the ultrafast scanning mode, we have observed that capsid stiffening is associated with rounding of the core, which returns to an elongated shape upon relaxation [ 66 ]. This suggests that the flexibility of the capsid endows it with elastic properties which allow it to accommodate the stresses during reverse transcription without breaking.…”
Section: Reverse Transcription Promotes Hiv-1 Uncoatingmentioning
confidence: 99%
“…It is therefore likely that the observed changes in sedimentation velocity of the RTCs at different times post-infection [ 34 ] reflect the different capsid core morphologies brought forward by the conversion of the viral genome from RNA into a double-stranded DNA. This notion is supported by recent atomic force microscopy analysis of the capsid core in the presence of IP 6 , showing step-wise, discrete core deformations that coincide with the three steps of reverse transcription, with progressive loss of core integrity [ 25 ].…”
Section: Ca and Reverse Transcriptionmentioning
confidence: 72%
“…Near-atomic reconstruction of the HIV-1 capsid core by cryo-EM also revealed that the NTD–CTD linker domains are flexible, allowing some degree of asymmetry of the capsid hexamer, which can curve at an angle of about 20°, thus contributing to the overall curvature of the capsid core itself [ 16 , 23 ]. In agreement with this notion, molecular dynamics simulations predicted that the capsid core oscillates, suggesting that structural flexibility might allow the core potentially to adopt different conformations in response to allosteric cues, such as co-factor binding [ 24 ] or reverse transcription [ 25 ].…”
Section: The Capsid Structure Reveals Several Binding Pocketsmentioning
confidence: 89%
“…In vitro studies using atomic force microscopy (AFM) suggested that reverse transcription increases the pressure inside the core triggering uncoating [ 17 ]; this agrees with our previous assessment that uncoating is initiated after first strand transfer during reverse transcription [ 16 ]. Rankovic et al have recently suggested that different stages of reverse transcription induce mechanical changes in the capsid that progressively remodel the viral core to prime it for uncoating [ 62 ]. By using an impressive in vitro replication system, Christensen et al imaged viral cDNA loops extruding from partially uncoated cores [ 63 ].…”
Section: Nuclear Entry and Reverse Transcriptionmentioning
confidence: 99%